Analisis pH Air pada Lahan Rawa Pasang Surut Sebagai Potensi MINAPADI di Desa Sungai Dua - Siti Lestari; Muhammad Sumsanto; Puteri Anugerah; Selly Ratna Sari; Pikha bimon (Clarias : Jurnal Perikanan Air Tawar, 2021)
The waters of South Sumatra have considerable potential for catching and cultivating fish consisting of snakehead fish, sepat, catfish and others. The opportunity to conduct aquaculture in South Sumatra is still wide open, especially in swamp waters because almost half of the swamp waters have not been fully utilized. So this study puprposed to determine the feasibility of the inlet and outlet water pH in tidal swamp to minapadi in Sungai Dua village, Banguasin Regency, South Sumatra. This research was carried out from October to December 2020. Samples were taken twice at the beginning of the first rice planting and at the second stage of rice planting. Sampling was carried out at five water points. The data obtained were analyzed descriptively using a table. The results of the study that tidal swamp land can be used for Minapadi because the pH value ranging from 4-6 is still tolerant to endemic fish because it is filtered lime at the water inlet.